Assessment of environmental management practices in the hotel industry towards sustainable tourism in Malaysia - Abdu Bakori, Kasimu (2011)
The, primary aim of this study is to investigate hotel industry participation in environmental management practices in Kuala Lumpur and the state of Selangor, Malaysia. The study attempts to achieve three main objectives: (1) to identify the current environmental management practices been implemented by hotel organisations; (2) to examine the factors related to the implementation of sustainable tourism initiatives; and, (3) to identify the perceived benefits in adopting sustainable tourism programs. Therefore, this study provides a focused academic analysis of these issues within the context of the hotel industry. This study employs a quantitative approach in which data are collected by distributing questionnaires as the primary data collection method. In line with the first objective, descriptive statistics were used to determine the level of sustainable tourism practices among the sample hotels. The findings revealed that, generally, 68% of the environmental practices investigated (which consists of energy, water and waste management), in the study has been widely adopted by the hotels. Therefore environmental management system (EMS) that supports sustainable management has been widely practiced. The second objective focuses on examining the factors influencing hotels’ participation in sustainable tourism initiatives. The Spearman rho correlation analysis was performed to conduct the hypothesis testing on the factors related to the implementation of Sustainable Tourism Practices (STP). The correlation results confirmed that there were significant positive relationship between training and STP (rs=. 504, p= .000); and between policy and STP (rs= .362, p= .005). Similarly, results of correlation analysis revealed a significant positive correlation between knowledge and STP (rs= .400, p= .002), also, the study found a significant positive correlation between incentive and STP (rs= .530, p= .000). Therefore, the results have found new evidences that training, policy, knowledge, and incentives are related to STP. As for the third objective, this study found that most of the hotel managers indicated the benefit of improved image as their major reason for implementing sustainable tourism practices. This study has made contributions to both academic and industry practices. Based on the study findings, it is suggested that government and other stakeholders in tourism development should intensify efforts to educate hoteliers on the importance of implementing STP in their hotels. It is therefore expected that hotel managers in Malaysia will utilise the findings of this study to improve on environmental management practices in their hotels.